PENYAKIT AKIBAT KERJA DAN KECELAAN KERJA SMK N 1 MUBARKEYA - Khairuman; Deviana; Ummi Elviyati; Salmalia; Nurul Hasanah S; Witri Aulia; Nada Permata; Izzatul Munira; Rifka Aulia; M.Irhas Junian Syahputra; Muhammad Aidil Fitra (Jurnal Dremi (Demi Pengabdi Masyarakat), 2025)
Occupational diseases and work accidents are serious problems in schools that have a major impact on the health and safety of workers. reviews several real cases in Indonesia. By analyzing these incidents, it emphasizes the importance of implementing an effective occupational health and safety (K3) program to prevent accidents and occupational diseases. Apart from that, the role of regulations and supervision to ensure school compliance with K3 standards is also discussed. Increase awareness and education regarding K3 in order to create a safer and healthier work or school environment for all students. This research method uses a descriptive-qualitative approach to analyze the factors that cause work accidents. The aim is to analyze the causal factors, the results of research on work accidents, work-related diseases, and the effectiveness of Occupational Health and Safety programs to discuss the impacts that arise and the factors that cause work.